Prevalence and Evaluation of Complications in Valvular Heart Disease Patients In Tertiary Care Hospital - Rafeh Mariya, Amtul; Mubeen Batool, Arshiya; Polamuri, Sri Praneeth; Koneru, Anupama; Srinivas Nayak, S. P (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: One of the major outcomes of valvular heart disease have been chronic complications that in turn have led to the reduced quality of life of patients. These complications have indeed caused immense burden on the health care system and has led to increased mortality rate. Objective: To determine prevalence rate and to evaluate complications of valvular heart disease patients. Methods: This is a cross sectional-based study carried out in a single hospital in Hyderabad, India. The survey was carried out over a year in India. The source of data collection was through case sheets and lab reports. Results: Of the total 102 subjects, valvular diseases were more prevalent in the age group of 51-60 and females were found to be more affected than males. Complications were less or equal to no after the procedure of valve replacement was performed in patients with severe cases though some patients showed complications even after surgery, but were stable after a long time of monitoring. 1% of valve prolapse cases were seen and 3% deaths due to the disease. St.jude mechanical valve of different sizes, 19 EPR biological valve and aortic valve implants were majorly used for valve replacement procedure. Conclusion: The study concludes that valvular diseases are more prevalent in the age group 51-60, and females were more affected by valvular diseases than males. Hypertension and diabetes mellitus were found to be the major comorbidities in valvular heart disease patients.